2022
DOI: 10.1136/bmjopen-2021-050871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of change in emergency care knowledge and skills among front-line healthcare providers in Ukraine with the Basic Emergency Care course: a pretest/post-test study

Abstract: ObjectiveEvaluate the change in participant emergency care knowledge and skill confidence after implementation of the WHO-International Committee of the Red Cross (ICRC) Basic Emergency Care (BEC) course.DesignPretest/post-test quasi-experimental study.SettingMechnikov Hospital in Dnipro, Ukraine.ParticipantsSeventy-nine participants engaged in the course, of whom 50 (63.3%) completed all assessment tools. The course was open to healthcare providers of any level who assess and treat emergency conditions as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Limited data have emerged from the war in Ukraine on the roles and effects of early care trauma systems. Our results align with those of Kivlehan et al who reported significant improvements in knowledge and confidence among Ukrainian participants in a 5-day WHO-ICRC Basic Emergency Care course carried out in 2022 13…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Limited data have emerged from the war in Ukraine on the roles and effects of early care trauma systems. Our results align with those of Kivlehan et al who reported significant improvements in knowledge and confidence among Ukrainian participants in a 5-day WHO-ICRC Basic Emergency Care course carried out in 2022 13…”
Section: Discussionsupporting
confidence: 92%
“…Our results align with those of Kivlehan et al who reported significant improvements in knowledge and confidence among Ukrainian participants in a 5-day WHO-ICRC Basic Emergency Care course carried out in 2022. 13 Epstein et al compared some of the lessons learnt from the US 'Global War on Terror' to the work of their group in supporting surgical care services in Ukraine. 14 Riley has examined the potential lessons from the war for largescale NATO led medical operations 15 and Zasiekina has explored the impact of Post Traumatic Stress Disorder at community level.…”
Section: Open Accessmentioning
confidence: 99%
“…For the first time, the armed conflict in Ukraine generated a paper included in the GEMLR. Kivlehan et al 68 . implemented the World Health Organization Basic Emergency Care (BEC) course for the first time in a European context and during an active humanitarian conflict and demonstrated improvement in emergency care knowledge and skill performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the pilot BEC programs in Zambia, Tanzania, and Uganda, additional iterations have been implemented in emergency facilities in Nigeria, Sierra Leone, Ukraine, and Kiribati and adapted for each clinical context [30][31][32][33]. In these cases, knowledge acquisition was similarly measured by comparing pre-and post-course assessments.…”
Section: Plos Onementioning
confidence: 99%